Mixed education and quality standard in the university teaching: a literature review - Al-Momani, Mohammad Omar; Rababa, Elham Mahmoud (International Journal for Educational and Vocational Studies)
Educators are constantly looking for the best ways and techniques to provide an interactive learning environment that attracts students' interest in exchanging opinions and experiences. With the advent of the Internet and the use of modern information and communication technology, the development of distance learning is called e-learning, which focuses on introducing advanced technology into the educational process, and transforming traditional classes into virtual classes. The traditional classes and the replacement of the default classes. This article will review the literature and theoretical perspectives that contain relevant studies